Chemical separations of a flerovium homolog using macrocyclic extractants - Ahrens, Nicole Lynn, author; Sudowe, Ralf, advisor; Brandl, Alexander, committee member; Johnson, Thomas, committee member; Omur-Ozbek, Pinar, committee member (Colorado State University. Libraries, 2024)
The placement of elements on the Periodic Table is governed by their fundamental chemical properties, maintaining specific trends when they are situated in order of increasing atomic number according to periodic law. When it comes to the heaviest of elements like flerovium (Fl), however, relativistic effects have the potential to alter their chemical behavior relative to lighter elements of the same group. The chemistry of Fl must be studied in order to confirm its placement on the Periodic Table, posing a unique challenge due to its low production cross-sections and short half-life. A chemical system capable of exceptionally fast and selective separations is required to achieve this extreme chemistry task. Such a system can be developed for Fl using its lighter homolog Pb. Two classes of macrocyclic extractants were explored with the aim of developing a chemical separation system for ultimate use in a Fl experiment. Specifically, crown ethers and calixarenes were evaluated as extractants for Pb using extraction chromatography and solvent extraction techniques. In these studies, crown ethers containing both oxygen and sulfur as bridging atoms were found to be ineffective Pb extractants in hydrochloric acid matrices. Unsupported calix[4]arenes also possessing bridging oxygens and sulfurs in various oxidation states were observed to be similarly ineffective but illustrated that the selectivity of calixarenes for Pb can be enhanced by modification of the outer functional groups as well as the bridging atoms. Though not effective as Pb extractants on their own, a significant synergistic effect was observed in EXC studies of a mixed system employing Eichrom Pb resin and a mobile phase containing 4-sulfocalix[4]arene with kinetics suitable for a Fl experiment. A similar SX system was then developed using the same crown ether extractant found on Pb resin with carbon tetrachloride as the organic diluent, but Pb extraction by the system was negligible.
Keywords: flerovium; radiochemistry; extraction; separation; lead